Surface modified iron magnetic nanoparticles assisted Fenton digestion and extraction method for cadmium determination - Ayyildiz, Merve Firat; Saylan, Meltem; Bozyigit, Gamze Dalgic; Chormey, Dotse Selali; Ozdemir, Oguz Kaan; Buyukpinar, Cagdas; Bakirdere, Sezgin (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2021)
This study presents a Fenton digestion method for milk samples based on UV irradiation for cadmium deter-mination using flame atomic absorption spectrometry. The method was developed as an alternative to micro-wave digesters, using very basic apparatus and easy to acquire chemicals. Fenton digestion process was performed by the help of citric acid coated magnetic nanoparticles. Optimum conditions of the digestion process were applied to milk samples to evaluate analytical performance of the method. Limit of detection and limit of quantification values calculated for cadmium in milk were 0.53 and 1.8 mg/L, respectively. The method was applied to three different milk samples to validate the method's suitability and accuracy. Percent recovery values calculated for the samples spiked at two different concentrations ranged between 86 and 111%. Due to differ-ences in the content of the spiked and control/standard milk samples, exact matrix matching calibration strategy using the same brand of milk sample in the preparation of calibration standard was employed and the accuracy of cadmium quantification was greatly enhanced (approximate to 100%).
Keywords: Cadmium; Fenton digestion; FAAS; UV-Radiation; Milk; SOLID-PHASE EXTRACTION; PLASMA; WATER; Biochemistry & Molecular Biology; Chemistry